2014
DOI: 10.3389/fnsys.2014.00048
|View full text |Cite
|
Sign up to set email alerts
|

The claustrum in review

Abstract: The claustrum is among the most enigmatic of all prominent mammalian brain structures. Since the 19th century, a wealth of data has amassed on this forebrain nucleus. However, much of this data is disparate and contentious; conflicting views regarding the claustrum’s structural definitions and possible functions abound. This review synthesizes historical and recent claustrum studies with the purpose of formulating an acceptable description of its structural properties. Integrating extant anatomical and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
215
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(224 citation statements)
references
References 86 publications
(198 reference statements)
9
215
0
Order By: Relevance
“…The remaining cells are Golgi type II neurons, lacking spines, with axons that do not project outside of the body of the claustrum. These are thought to be inhibitory-like interneurons that provide a substrate for local information processing (Mathur, 2014). Anterograde labeling studies in the cat have demonstrated the abundance of claustral terminals in the inner parts of layers III (IV in some PFC zones) and VI, as well as in layer I, but layer V is remarkably free of terminals (Clascá et al, 1992).…”
Section: H a Role For The Claustrum?mentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining cells are Golgi type II neurons, lacking spines, with axons that do not project outside of the body of the claustrum. These are thought to be inhibitory-like interneurons that provide a substrate for local information processing (Mathur, 2014). Anterograde labeling studies in the cat have demonstrated the abundance of claustral terminals in the inner parts of layers III (IV in some PFC zones) and VI, as well as in layer I, but layer V is remarkably free of terminals (Clascá et al, 1992).…”
Section: H a Role For The Claustrum?mentioning
confidence: 99%
“…Nevertheless, it is generally accepted today that the claustrum exhibits widely distributed reciprocal anatomic projections to virtually all regions of the cortex as well as to many subcortical structures, including the hippocampus, amygdala, and caudate nucleus. Substantial evidence now exists that the major target of claustral projections is the cortex, and that the major input to the claustrum comes from the cortex (see reviews by Smythies et al, 2012Smythies et al, , 2014Baizer et al, 2014;Mathur, 2014;Torgerson and Van Horn, 2014).…”
Section: H a Role For The Claustrum?mentioning
confidence: 99%
“…The neural circuit mechanisms underlying top-down control are, however, poorly understood. Identified candidate top-down circuits arising from frontal cortices include direct inputs to posterior sensory cortices, thalamus, and claustrum (Miller and Buschman, 2013; Zhang et al, 2014; Mathur, 2014). Given that prefrontal cortex neurons can encode task performance differentially based on projection target (Otis et al, 2017), it is critical to determine which signals are being propagated to claustrum, for instance, and how these signals (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As we have alluded to already, and perhaps understandably given the elaborate claustral connectome, the possible functions of the claustrum have received considerable attention, with many hypotheses posed (Goll et al, 2015;Mathur, 2014;Remedios et al, 2010Remedios et al, , 2014Smythies et al, 2012b). Most recently, two related articles (Smythies et al, 2012a;Yin et al, 2016) suggest that complex connectivity and organisation of the claustrum is Like cortico-thalamic inputs, cortico-claustral inputs are predominantly derived from cortical layer 6, while claustro-cortical inputs are predominantly to cortical layer 4, suggesting that they may comprise a driver input rather than a modulatory one.…”
Section: Claustral Functionsmentioning
confidence: 99%